Gambaran Perilaku Wanita Hamil dalam Melakukan Antenatal Care saat Pandemi Covid-19 di Puskesmas Rawat Inap Sidomulyo, Kota Pekanbaru - Refiani, Diny; Dewi, Yulia Irvani; Utami, Sri (Health Information : Jurnal Penelitian, 2021)
The COVID-19 pandemic has a major impact on Maternal and Child Health (MCH) services, which causes a significant decrease in the number of visits by pregnant women. This research aims to determine how pregnant women behave in doing antenatal care during the COVID-19 pandemic. This research used a quantitative descriptive design. The sample of this research was 40 trimester III pregnant women who performed ANC examination with accidental sampling technique from November 2020 to January 2021. The analysis used was univariate. The results of this research showed that the majority of pregnant women aged 20-35 years (productive age) with a total of 34 respondents (85%), there were 21 respondents with High School as the latest education (52,5%) and also 26 total respondents (65%) who did not have a job. The behavior of pregnant women in doing ANC during the COVID-19 pandemic showed positive behavior results with 21 respondents (52,5%) almost the same as the result of negative behavior results that gained 19 total respondents (47,5%). Most of the pregnant womens' behavior based on the ANC implementation guidelines during the COVID-19 pandemic were negative, with a total of 24 respondents (60%). On the other hand, most of the pregnant womens' behaviors based on the prevention of COVID-19 by implementing the health protocol were positive, with 25 respondents (62,5%). The behavior of pregnant women in doing ANC during COVID-19 is almost the same between negative behavior and positive behavior, therefore for pregnant women need to be more aware of choosing good behavior during pregnancy to get through the period of pregnancy in a better way, give birth safely, and give birth to a healthy baby.